De la igualdad económica a la soberanía política. Una reconsideración del pensamiento distributista - García, Juan Carlos Utrera (Cauriensia, 2022)
In order to outline its theoretical proposal, this work intends to analyze the links of distributism with Christian thought, and more specifically, with the social and political doctrine of Catholicism. This entails pointing out, within a common theoretical framework, some distinctive elements of the former regarding the contemporary social doctrine of the Church as it appears in its founding texts, as well as its radical and uncompromising criticism of modernity and any socioeconomic model of a capitalist or socialist nature. Finally, the political scope of the economic postulates of distributism and the validity of certain postulates for some current alternative movements are pointed out.